Vertical collapse safety margin assessment for steel frames against earthquake-induced loss of column. (November 2019) - Tantely, Jeriniaina Sitraka; He, Zheng
Abstract: A quantifiable approach measuring the seismic structural collapse under sudden column removal is proposed using the interaction of the vertical collapse margin ratio ( CMR V ), the demand-to-capacity ratio ( DCR ) and the robustness ( R ). The assessment of CMR V needs the identification of the vertical maximum considered earthquakes. A classification of the ground motions based on the vertical-to-horizontal ( V / H ) ratios was used to obtain the vertical design spectrum. Six schemes of steel structures with various scenarios of sudden column removal were investigated to extract CMR V, DCR, and R . Then, a nonlinear regression analysis allows finding a general formulation of CMR V . A 15-story steel structure validates the proposed formulation of the CMR V . The two paths for estimating the minimum CMR V ( CMR V, min ) were the use of the recommended value of DCR and the minimum value of R inside the approximated CMR V expression, and the probabilistic distribution of CMR V, min from the analyses of different beam deformation states. The study of eighteen archetypes with 119 scenarios of sudden column removal reveals the value of the CMR V decreases when the V / H or/and DCR increase. The new maximum values of DCR with respect to R and its precise ranges are found with the use of the contour curves of CMR V, min . Highlights: The proposed classification of the vertical component of the earthquakes is based on the V / H ratio. The structural safety diminishes with the increase of V / H ratio and DCR . CMR V, min allows estimating the new range of values for DCR and R . An improved value of DCR can reduce the structural cost while preserving the structural strength.